2019
DOI: 10.1055/a-0894-9400
|View full text |Cite
|
Sign up to set email alerts
|

Sexualpädagogik in der Sekundarstufe I in Österreich

Abstract: Zusammenfassung Einleitung Das WHO-Regionalbüro für Europa und die Bundeszentrale für gesundheitliche Aufklärung (BZgA) haben 2010 Standards für Sexualerziehung in Europa veröffentlicht, um einen Überblick über die Themen der Sexualerziehung zu geben, die in der Schule angepasst an verschiedene Altersstufen behandelt werden sollten. Sie sollen gewährleisten, dass Sexualkundeunterricht in Europa ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Also in 2019, Depauli et al conducted a study on 9,196 Austrian parents and students (in the age range of 13-15 years) to examine aspects of success in sex education and the importance of topics covered by WHO standards. The results indicated that both parents and students considered sex education to be of high importance, and in addition, parents showed a special interest in teaching the basic principles of rights and protection of children and adolescents, as well as health and biological principles (34). Ziaei and Gorji (2018) in their study have shown that the use of interventional counseling program of communication skills and sexual health signi cantly increases the frequency of mother-daughter dialogue on sex compared to the control group (35).…”
Section: Discussionmentioning
confidence: 99%
“…Also in 2019, Depauli et al conducted a study on 9,196 Austrian parents and students (in the age range of 13-15 years) to examine aspects of success in sex education and the importance of topics covered by WHO standards. The results indicated that both parents and students considered sex education to be of high importance, and in addition, parents showed a special interest in teaching the basic principles of rights and protection of children and adolescents, as well as health and biological principles (34). Ziaei and Gorji (2018) in their study have shown that the use of interventional counseling program of communication skills and sexual health signi cantly increases the frequency of mother-daughter dialogue on sex compared to the control group (35).…”
Section: Discussionmentioning
confidence: 99%